Photosynthetic response to light and temperature in Laminaria digitata gametophytes from two French populations. Issue 1 (2nd January 2016) - Delebecq, Gaspard; Davoult, Dominique; Janquin, Marie-Andree; Oppliger, Luz Valeria; Menu, Dominique; Dauvin, Jean-Claude; Gevaert, François
ABSTRACT: Given the growing body of evidence on the general decline of kelp beds worldwide, it is crucial to understand the physiological responses of kelp gametophyte stages to environmental parameters. We investigated the physiological responses to light and temperature of gametophytes from two populations of Laminaria digitata in contrasting environments along the French coast of the English Channel. Gametophytes of both populations were highly tolerant of high light through an efficient down-regulation of photosynthesis triggered by the activation of the xanthophyll cycle. Temperature increases promoted photosynthesis and photosystem II showed high resistance to short-term exposure to high temperatures currently encountered in the field. Gametophytes from the two sites displayed some differences in their pigment content and photosynthetic characteristics, but low replication and difference in time of sampling precluded tests of potential local adaptation to the light conditions at each site, as observed in previously published results on adult sporophytes. Gametophytes of L. digitata appeared to be resistant to irradiation and temperature conditions currently experienced in the field, confirming their role in persistence of kelp species under stressful environmental conditions.